Pengaruh Gaya Kepemimpinan Transformasional, Lingkungan Kerja, dan Kompensasi terhadap Kinerja Pegawai Universitas Terbuka dengan Kepuasan Kerja Sebagai Variabel Intervening - Dyah Palupi Setiyoningrum; Achmad Fauzi; Maman Rumanta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of transformational leadership style, work environment, and compensation on the employee performance of Universitas Terbuka, with job satisfaction serving as an intervening variable. A quantitative approach with an explanatory research design was employed. The study population consisted of 2,651 Universitas Terbuka employees; a sample of 400 respondents was determined using Slovin's formula, while the data analyzed in this study were derived from 189 respondents. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM), encompassing outer model testing, inner model testing, hypothesis testing, and mediation analysis using Variance Accounted For (VAF). The results indicate that transformational leadership style has a negative and significant effect on employee performance (β = -0.164; p = 0.046) but does not significantly affect job satisfaction. The work environment does not significantly affect employee performance (β = 0.103; p = 0.416) but has a positive and significant effect on job satisfaction (β = 0.459; p = 0.000). Compensation does not significantly affect employee performance (β = 0.022; p = 0.843) but has a positive and significant effect on job satisfaction (β = 0.459; p = 0.000). Job satisfaction has a positive and significant effect on employee performance (β = 0.533; p = 0.000). Furthermore, job satisfaction does not mediate the effect of transformational leadership style on performance; however, it partially mediates the effect of the work environment on performance (β = 0.245; p = 0.001) and fully mediates the effect of compensation on performance (β = 0.245; p = 0.000). The study concludes that job satisfaction is a crucial mechanism for enhancing the performance of Universitas Terbuka employees, particularly in mediating the impact of the work environment and compensation on performance; conversely, transformational leadership style did not succeed in improving either employee performance or job satisfaction within the context of this study. Keywords: Transformational Leadership Style, Job Satisfaction, Compensation, Employee Performance, Work Environment